Akuntansi Dan Teknologi: Bagaimana Perubahan Teknologi Mempengaruhi Pekerjaan Akuntan: Indonesia - Marlinda Effendi; Umi Kholilah; Lizianil Azizah; Sri Wahyuningsih; Gunawan Aji (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
The development of information technology has brought significant impacts to various aspects of people's lives, including in the field of accounting. From the mid-1960s to the current digital era, technological transformation has changed the way businesses operate, created new business models, and created a complex digital ecosystem. In this context, accounting theory needs to be continuously adapted to technological developments and changes in consumer behavior to remain relevant and effective.